The Impact of Personality on Employee Performance Improvement: The Role of Mediation by Organizational Citizenship Behavior - Ali Jufri; Pebi Kurniawan; Istianah Istianah (Dinasti Publisher, 2025)
The quality of human resources is a crucial element in driving economic recovery and a key determinant of long-term competitiveness and productivity. Amid the advancement of technology and the complexity of modern organizations, companies demand optimal employee performance, which is partly influenced by the strength of personality character. This study aims to analyze the influence of personality on employee performance by considering the mediating role of organizational citizenship behavior (OCB). The research method used is quantitative, by distributing questionnaires to 100 randomly selected respondents. The research results show that (1) personality has a positive and significant impact on employee performance; (2) temperament also positively and significantly affects the increase in OCB; (3) OCB significantly improves employee performance; and (4) OCB proves to be a significant mediator in the relationship between personality and employee performance. These findings emphasize the value of strengthening personality traits and positive organizational behavior as strategies for performance improvement in the workplace.